Особенности оценивания неопределенности измерений типа А на основе байесовского подхода - Боцюра, А. О.; Захаров, И. П. (харківський університет повітряних сил, 2015)
The revision of GUM is described, the basic peculiarities of evaluation of standard and extended measurement uncertainties of type A based on the Bayesian approach is reviewed.
Peculiarities of evaluation of measurement uncertainty type a based on a bayesian approach
Keywords: measurement uncertainty; Bayesian approach; probability density function